Thermophilic facultative anaerobic bacteria of the genus Geobacillus from bottom sediments of Lake Baikal - T. A. Khanaeva; O. N. Pavlova; S. M. Chernitsyna; I. A. Khalzov; A. V. Khabuev; A. A. Nikonova; A. S. Novikova; T. I. Zemskaya (Acta Biologica Sibirica, 2017)
Pure culture of thermophilic facultative anaerobic microorganism was isolated from surface sediment of methane seepage Posolsk Bank. New strain Geobacillus sp. PB15/Grf7geo does not differ from the typical strains by morphological and physiological-biochemical properties. It is able to withstand of wide temperature range with optimum growth between 55–60 °C. Chemoorganotroph. Phylogenetic analysis of the 16S rRNA sequence of the strain showed 97 % identity to cultivated strains of this genus. The strain forms a common clade with uncultivated representatives and does not cluster with sequences of cultivated strains within the genus Geobacillus in the phylogenetic tree. Strain Geobacillus sp. PB15/Grf7geo has been deposited to the collection of the VKM (=VKM B–3150T).